2021
DOI: 10.35848/1882-0786/abd4c5
|View full text |Cite
|
Sign up to set email alerts
|

A drastic increase in critical thickness for strained SiGe by growth on mesa-patterned Ge-on-Si

Abstract: We demonstrate that the critical thickness for Ge-rich strained SiGe layers can be drastically increased by a factor of more then two by means of growth on mesa-patterned Ge-on-Si. The Si0.2Ge0.8 layer grown on sub-millimeter mesa Ge-on-Si is fully strained and free from ridge roughness, while the same Si0.2Ge0.8 layers grown on unpatterned Ge-on-Si and a Ge substrate are partially strain-relaxed with the surface covered by high-density ridge roughness. This demonstrates that the proposed patterning method can… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

1
6
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
7

Relationship

2
5

Authors

Journals

citations
Cited by 8 publications
(7 citation statements)
references
References 32 publications
1
6
0
Order By: Relevance
“…[43]. On top of the HT-Ge layer, a 70-nm-thick phosphorus (P)-doped n-Si 0.1 Ge 0.9 (111) layer is grown by MBE at 350 • C [47]. Finally, a 7-nm-thick P δ-doped Ge layer with a 0.3nm-thick Si layer is grown on top of the spin-transport layer for the Schottky tunnel conduction of electrons in spin-transport measurements [48].…”
Section: Resultsmentioning
confidence: 99%
“…[43]. On top of the HT-Ge layer, a 70-nm-thick phosphorus (P)-doped n-Si 0.1 Ge 0.9 (111) layer is grown by MBE at 350 • C [47]. Finally, a 7-nm-thick P δ-doped Ge layer with a 0.3nm-thick Si layer is grown on top of the spin-transport layer for the Schottky tunnel conduction of electrons in spin-transport measurements [48].…”
Section: Resultsmentioning
confidence: 99%
“…17) Next, a strained n-doped Si 0.1 Ge 0.9 layer with a thickness of 70 nm was grown at 350 °C to form a spin transport layer. 18) A Ge cap layer with phosphorus (P) delta (δ) doping and an ultrathin Si layer were further stacked on top of this layer to enable the use of Schottky tunneling conduction of electrons in the spin transport measurements. 19) To form a highly ordered Co 2 MnSi Heusler alloy on top of it, an ultra-thin iron (Fe) layer is inserted between the Co 2 MnSi and the Ge cap, 20) where Co 2 MnSi is a highly efficient ferromagnetic spin injector material for semiconductors.…”
Section: Methodsmentioning
confidence: 99%
“…However, there are still very few reports on experimental investigations of crack formation in tensile-strained SiGe layers. Recently, we have been studying the initial stage of defect formation for tensile-strained SiGe layers, and have experimentally determined the critical thickness for defect generation and resultant strain relaxation [17][18][19][20][21]. We have also shown that cracks and accompanying surface ridge roughness appear in tensile-strained SiGe epilayers when the thickness of the epilayer exceeds the critical thickness [18].…”
Section: Introductionmentioning
confidence: 99%